Zakat and the Empowerment of the Hardcore Poor in the 21st Century - Abdul Hamid, Solahuddin; Hamid, Mohd Liki (Advance Scientific Research, 2020)
Numerous definitions and concepts of poverty have been put forth as a result of different beliefs, cultural backgrounds, life philosophies or social norms. Individuals’ needs are also different and contingent on their social demographics. Nevertheless, the issue of poverty is tied to the definitions and concepts that refer to specific unfulfilled needs or wants. Islam is more advanced in defending the rights of the poor with the implementation of zakat (obligatory charity in the form of alms-giving) with no prior objection or request from the poor of their rights from those who are wealthy. Zakat is not only a system that relies on personal sympathy or individual’s donations, it is also a socio-economic system, in which its implementation is regulated by the government. Irrespective of this, zakat distribution system warrants effective strategy in overcoming complex poverty issues that have fettered the society today. The poverty eradication program has been considered as inefficient since the same target groups remain poor in the long run. At the same time, there is a yearly increase in the number of new poor people. This article discusses the efficiency of the management of zakat distribution scheme in the context of empowering the hardcore poor based on the measurement and standard set by the religion as well as what the poor individuals need in the 21st century. The empowerment program requires total commitment from the government, institutions of zakat and the society. In addition, individuals that are shackled by poverty have to develop their potentials and use the skills that they have to improve their lives. The success of this program will alleviate the number of the hardcore poor and minimize the burden carried by the zakat management institutions